ChemInform Abstract: Classical/Non‐Classical Polyoxometalate Hybrids. Issue 52 (6th December 2016) - Izarova, Natalya V.; Santiago‐Schuebel, Beatrix; Willbold, Sabine; Hess, Volkmar; Koegerler, Paul
Abstract: Cs4 Na3 H4 [Se2 Pd4 W14 O56 H] ·18H2 O·0.3Cs(OAc)·0.2Na(OAc) (I) and Cs9.5 Na2.5 [Se4 Pd4 W28 O108 H12 ] ·30H2 O (II) are precipitated with aq.